Infantile fibromatosis colli: torticollis with auspicious outcome - Sharma, Prasidutt; Agarwal, Shubhi; Choudhury, Khurshed A.; Udagi, Sharanaprabhu (International Journal of Contemporary Pediatrics, 2024)
Among the various causes of infantile torticollis fibromatosis colli (FC) is a scarce one. Although it’s a benign condition it causes momentous disquiet in parents. Neck swelling with history of difficult instrument delivery is a classical allusion towards FC. Proliferation of sternocleidomastoid (SCM) muscle is the major cause. Presentation is commonly at 2-6 weeks of age with complaints of swelling or torticollis mostly unilateral, rarely bilateral. A 5-week-old male baby presented with swelling on the right side of neck and diagnosed with FC. We evaluated potential diagnostic modalities in this patient and concluded their usefulness and importance in various presentations.